P53 The associations between common mental disorders (anxiety and depression) and socio-economic and demographic factors in two russian cities. (September 2018) - Cook, S; Kudryavtsev, AV; Bobrova, N; Malyutina, S; Leon, DA
Abstract : Background: Common mental disorders (anxiety and depression) are important public health concerns worldwide. There is very little evidence about the risk factors for these in Russia despite high rates of associated markers: suicide and alcohol-attributable mortality. The aim of this study was to investigate the associations between common mental disorders and socio-demographic factors in the Russian adult population. Methods: Data were from two population-based cross-sectional surveys conducted in 2016–17 among men and women aged 35–69 years old resident in the Russian cities of Arkhangelsk and Novosibirsk as part of the International Project on Cardiovascular Disease in Russia (IPCDR). Participants were recruited and interviewed in their homes. Information collected included questions on socio-demographic factors (marital status, education, employment and financial status). Depression was defined as a score of ≥10 on the PHQ-9 instrument and anxiety as a score of ≥10 on the GAD-7 instrument. Financial status was on a 5-point scale from not enough money for food to no financial constraints. Logistic regression was used to estimate effects of socio-demographic factors on anxiety and depression adjusting for age, sex and city and then for all other socio-demographic variables. Volume of alcohol consumed per year and problem drinking defined as CAGE score ≥2 were entered into the models at the last step in order to assess the effect on the associations of interest. Results: After adjustment for all socio-demographic variables depression was more prevalent among women (OR 1.93 95% CI 1.53, 2.44), those who were divorced or separated compared to married (OR 1.46 95% CI 1.10, 1.92), and not in regular employment (OR 1.49 95% CI 1.18, 1.88). There was a monotonic increase in risk of depression across the 5 categories of financial status from poorest to most affluent (p-value trend ≤0.001), with an OR >6 from bottom vs top category. Anxiety was more prevalent in women (OR 1.93 95% CI 1.42, 2.62). As with depression financial status also showed a strong inverse trend in risk (p<0.001). Education was inversely associated with depression and anxiety after adjustment for age, sex, and city but not after adjustment for other socio-demographic variables. The pattern of results remained similar after additional adjustment for alcohol use. Conclusion: Degree of financial hardship was strongly associated with symptoms of anxiety and depression even after adjustment for education, employment status and alcohol use. These findings underline the importance of considering social circumstances in addressing poor mental health.